WAR AND MEMORY: THE BATTLE OF PSYTTALEIA BEFORE HERODOTUS' HISTORIES. (21st December 2015) - PROIETTI, GIORGIA
Abstract: Summary: Before Herodotus, the Persian Wars underwent a multifaceted process of memorialization. As a consequence of the homeostasis of historical memory with contemporary social and semantic needs, pre-Herodoteanand Herodotean narratives about the same event can differ a great deal. This is well exemplified by the development of the historical tradition about the clash between Greeks and Persians at Psyttaleia. Reduced to a trivial appendix to the battle of Salamis by Herodotus, it seems instead to have played a prominent role within Athenian contemporary memory, as both literary and epigraphic evidence suggest. This paper first explores the different phases of the memorialization of Psyttaleia; second, it investigates the reasons for its re-shaping, arguing against political propaganda from above and dwelling instead on the deeper mechanisms of collective memory.